Active Smoking May Negatively Affect Response Rate, Progression-Free Survival, and Overall Survival of Patients With Metastatic Renal Cell Carcinoma Treated With Sunitinib. (5th December 2013) - Keizman, Daniel; Gottfried, Maya; Ish-Shalom, Maya; Maimon, Natalie; Peer, Avivit; Neumann, Avivit; Hammers, Hans; Eisenberger, Mario A.; Sinibaldi, Victoria; Pili, Roberto; Hayat, Henry; Kovel, Svetlana; et al.
Learning Objectives: Describe the association between risk factors for renal cell carcinoma and the outcome of sunitinib treatment for metastatic disease. Explain the impact of active smoking on the outcome of sunitinib-treated metastatic renal cell carcinoma. Discuss obesity, hypertension, and diabetes in relation to the outcome of sunitinib-treated metastatic renal cell carcinoma. Abstract: Background: Obesity, smoking, hypertension, and diabetes are risk factors for renal cell carcinoma development. Their presence has been associated with a worse outcome in various cancers. We sought to determine their association with outcome of sunitinib treatment in metastatic renal cell carcinoma (mRCC). Methods: An international multicenter retrospective study of sunitinib-treated mRCC patients was performed. Multivariate analyses were performed to determine the association between outcome and the pretreatment status of smoking, body mass index, hypertension, diabetes, and other known prognostic factors. Results: Between 2004 and 2013, 278 mRCC patients were treated with sunitinib: 59 were active smokers, 67 were obese, 73 were diabetic, and 165 had pretreatment hypertension. Median progression-free survival (PFS) was 9 months, and overall survival (OS) was 22 months. Factors associated with PFS were smoking status (past and active smokers: hazard ratio [HR]: 1.17, p = .39; never smokers: HR: 2.94, p < .0001), non-clear cell histology (HR: 1.62, p = .011), pretreatment neutrophil-to-lymphocyte ratio >3 (HR: 3.51, p < .0001), use of angiotensin system inhibitors (HR: 0.63, p = .01), sunitinib dose reduction or treatment interruption (HR: 0.72, p = .045), and Heng risk (good and intermediate risk: HR: 1.07, p = .77; poor risk: HR: 1.87, p = .046). Factors associated with OS were smoking status (past and active smokers: HR: 1.25, p = .29; never smokers: HR: 2.7, p < .0001), pretreatment neutrophil-to-lymphocyte ratio >3 (HR: 2.95, p < .0001), and sunitinib-induced hypertension (HR: 0.57, p = .002). Conclusion: Active smoking may negatively affect the PFS and OS of sunitinib-treated mRCC. Clinicians should consider advising patients to quit smoking at initiation of sunitinib treatment for mRCC. Abstract : An international multicenter retrospective study of sunitinib-treated metastatic renal cell carcinoma patients was performed to determine the association between outcome and the pretreatment status of smoking, body mass index, hypertension, diabetes, and other known prognostic factors. The results showed that active smoking may negatively affect the progression-free and overall survival of these patients.